1981
DOI: 10.1080/15287398109530038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brief and intermediate exposures to sulfate submicron aerosols and sulfate injections on cardiopulmonary function of dogs and tracheal mucous velocity of sheep

Abstract: Pulmonary mechanics of anesthetized dogs were not changed or were minimally altered by breathing the following compounds as submicron aerosols in concentrations up to 17.3 mg/m3 for 7.5 min: (1) sodium chloride (as a control), (2) sodium sulfate, (3) ammonium sulfate, (4) zinc sulfate, (5) zinc ammonium sulfate, (6) ammonium bisulfate, (7) aluminum sulfate, (8) manganese sulfate, (9) nickel sulfate, (10) copper sulfate, (11) ferrous sulfate, and (12) ferric sulfate. Submicron aerosols of these compounds in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…No effect was observed on tracheal mucociliary clearance in dogs exposed to 5 mg/m3 concentrations of 0.3 ,um aerosols while decided effects were observed at 1.0 mg/m3 concentrations of 0.9 ,um aerosols (70). These results are consistent with those of Sackner et al (76,77) who showed a lack of effect of 0.1 to 0.2 ,um H2SO4 aerosols on mucociliary clearance in sheep at concentrations up to 14 mg/m3. Mucociliary clearance effects have been noted in studies by others using H2SO4 particles greater than 0.5 ,um MMAD in size (70-72).…”
Section: Sulfuric Acid Mist (H2so4)supporting
confidence: 93%
See 1 more Smart Citation
“…No effect was observed on tracheal mucociliary clearance in dogs exposed to 5 mg/m3 concentrations of 0.3 ,um aerosols while decided effects were observed at 1.0 mg/m3 concentrations of 0.9 ,um aerosols (70). These results are consistent with those of Sackner et al (76,77) who showed a lack of effect of 0.1 to 0.2 ,um H2SO4 aerosols on mucociliary clearance in sheep at concentrations up to 14 mg/m3. Mucociliary clearance effects have been noted in studies by others using H2SO4 particles greater than 0.5 ,um MMAD in size (70-72).…”
Section: Sulfuric Acid Mist (H2so4)supporting
confidence: 93%
“…Last (89) has shown ammonium persulfate to produce results similar to those of sulfuric acid mist. Studies by Sackner (76,77) have shown no effects on pulmonary function in dogs or tracheal mucociliary clearance in sheep exposed to submicron aerosols (0.05-0.2 jim) at concentrations ranging from 4 to 9 mg/m3 of sodium sulfate, ammonium sulfate, zinc sulfate, zinc ammonium sulfate, ammonium bisulfate, aluminum sulfate, manganese sulfate, nickel sulfate, copper sulfate, ferrous sulfate, and ferric sulfate. The lack of response may be related to the small size of aerosols used.…”
Section: Other Sulfur Oxidesmentioning
confidence: 99%
“…33 In dogs and sheep, inhalation exposure to ≤1.9 mg/m 3 (1%) and ≤3.0 mg/m 3 (0.5%) of free zinc from Zinc Sulfate, respectively, for up to 4 h did not affect lung function (dogs) or tracheal mucous velocity (sheep). 96…”
Section: Acute Toxicity Studiesmentioning
confidence: 99%
“…Such research should also examine whether aerosol acidity, which was not directly measured as part of SCAMP, plays a role in solubilizing Fe. Additional research on the health effects of soluble fine particulate Fe is also warranted, because several studies 58,59 have failed to discover any statistically significant associations between Fe and adverse health end points, and another 60 has suggested that both the soluble and insoluble fractions of PM contain ionizable metals that can catalyze oxidative stress.…”
Section: Solubility Of Elements In Pm 25 At Steubenvillementioning
confidence: 99%